Fracturing the Idea of Tradition: On De Urbibus Inferis by Shimon Adaf - Shabat Nadir, Hadas (MiKAN, 2021)
In Shimon Adaf’s book De Urbibus Infenis, the protagonist undertakes a fascinating journey as he investigates the mystery of the origin of the seal of the Rose of Judea, the symbol of a secret Jewish doctrine founded in Morocco. Rumors of the origins of this secret doctrine have been spreading for thousands of years, from the time of the Sages to the present day, and the journey moves from Morocco to Berlin, through the development towns of southern Israel to Tel Aviv. To solve the riddle of the Rose of Judea, Adaf breaks down the boundaries of Hebrew language and genre and links worlds almost impossible to bring together: mysticism, science, detection, poetry, and prose. He examines the ways in which we can write about cultural traditions and transmit them as well as the place of personal and cultural memory in these processes. He explores how it is possible to create tradition even after long years of erasure of Moroccan culture by Zionism and after the son’s rebellion against the father and his refusal to follow in his footsteps. Adaf reworks the concept of tradition and examines its boundaries, splintering it into small pieces that he gives to his protagonists, but as he does so, they lose their meaning. This move turns tradition into a broken and shattered puzzle whose pieces do not fit. At the same time, the book is an act of gathering the fragments of tradition into one narrative that will always remain fractured. With the acts of shattering and gathering, Adaf seeks to read the East and tradition with fresh eyes, without relying on existing categories and in a way that can renew the discourse on Moroccan Jewish tradition as he imagines it.